Morphological Evolution of the Port‐City Interface of Algiers (16th Century to the Present) - Aouissi, Khalil Bachir (2021)
This article traces the centuries-long morphological development of Algiers’ port-city interface across four historically relevant time periods that together span from the dawn of the 16th century up until today. Through a diachronic and geo-historical approach, we identify and analyse the origins of Algiers’ persistent port-city divide. In doing so, the notion of the interface is interpreted as a spatial threshold between city and port, which nevertheless supports the material flows of both entities. As a multi-purpose area, the interface holds the potential to weave the disparate entities of a port city back together. To further complement this conceptual angle, we provide investigations of porosity that determine the differing degrees of connectivity between the city and port of Algiers. This is combined with a spatial-functional analysis of Algiers’ current port-city interface, which is ultimately characterised as a non-homogeneous entity composed of four distinct sequences. These results contribute to a better orientation of imminent plans for waterfront revitalisations in Algiers. Whereas the interface was long considered as some kind of no man’s land in the past, port and municipal authorities nowadays aim to turn the interface into a tool of reconciliation, and can do so by acting upon its potential porosity. Finally, this article’s critical examination of the previously neglected case of Algiers can and should also be considered as an applicable model for the continuing study of southern Mediterranean and African port metropolises in general, which share a particular evolution in the relations between city and port.